KEKERASAN DALAM RUMAH TANGGA DALAM PERSPEKTIF FIKIH EMANSIPATORIS (Ahkam: Jurnal Hukum Islam, 2022)
This article describes the act of beating done by a husband to his wife from the perspective of fikih, in response to Oki Setiana Dewi's lecture video clip. In Islam, the lecture is presumed as a form of legitimacy for Domestic Violence (KDRT). This article uses the literary method by searching the literature related to the topic to explain the most dominant side. The findings in the search shows that there are two different sides from the act of hitting a wife in the Household (KDRT). However, if a light stroke that leaves no traces is just a lesson, even so this kind of stroke is the last alternative for educating the wife. As a preventive measure, fikih offers action for how to build a household that chooses a partner who has a good religion and to avoids children from situations preventing violence.